Whole-genome analysis of influenza A(H1N1)pdm09 viruses isolated in Uganda from 2009 to 2011 - Byarugaba, Denis K.; Erima, Bernard; Millard, Monica; Kibuuka, Hannah; Lukwago, Luswa; Bwogi, Josephine; Mimbe, Derrick; Kiconco, Jocelyn B.; Tugume, Titus; Mworozi, Edison A.; Turner, Jasmine; Mckenzie, Pamela P.; et al. (Influenza and Other Respiratory Viruses, 2016)
We report a whole-genome analysis of 19 influenza A(H1N1)pdm09 isolates from four Ugandan hospitals between 2009 and 2011. The isolates differed from the vaccine strain A/California/07/2009 by three amino acid substitutions P100S, S220T, and I338V in the hemagglutinin and by two amino acid substitutions V106I and N248D in the neuraminidase proteins with consistent mutations in all gene segments distinguishing isolates from the 2009/2010 to 2010/2011 seasons. Phylogenetic analysis showed low genetic evolution, with genetic distances of 0%–1.3% and 0.1%–1.6% for HA and NA genes, respectively. The amino acid substitutions did not lead to antigenic differences from the reference strains.
Keywords: influenza A(H1N1)pdm09; Uganda; Whole-genome sequencing